ANALISIS PENGARUH AKSES KEUANGAN DIGITAL P2P LENDING, PENDIDIKAN, PENGANGGURAN DAN PERTUMBUHAN EKONOMI TERHADAP KETIMPANGAN PENDAPATAN DI INDONESIA - Dzikri Badaruzaman Al Haq; Thomas Andrian; Dian Fajarini (E-journal Field of Economics, Business and Entrepreneurship (EFEBE), 2025)
Income inequality continues to pose a significant challenge within Indonesia's economic landscape. This study aims to analyze the effect of digital financial access through peer-to-peer (P2P) lending, education, unemployment, and economic growth on income inequality across 34 provinces in Indonesia from 2020 to 2024. Grounded in the neoclassical theory of income distribution, human capital theory, and the Kuznets inverted-U hypothesis, this research employs a panel data regression model using the Fixed Effect Model (FEM). The results indicate that P2P lending, education, and unemployment have a significant effect on income inequality, with P2P lending, education and uneployment showing a negative relationship. Meanwhile, economic growth does not have a statistically significant effect on inequality